Integrating metallic nanoparticles of Au and Pt with MoS2–CdS hybrids for high-efficient photocatalytic hydrogen generation via plasmon-induced electron and energy transfer. Issue 42 (17th May 2017) - Chen, Kai; Ma, Liang; Wang, Jia-Hong; Cheng, Zi-Qiang; Yang, Da-Jie; Li, Ying-Ying; Ding, Si-Jing; Zhou, Li; Wang, Qu-Quan
Abstract : A mechanism of high-efficient photocatalytic hydrogen generation via plasmon-induced electron and energy transfer was demonstrated. Abstract : Semiconductor-based photocatalytic H2 generation is a promising approach to convert solar energy, but single-component photocatalysts still suffer from low efficiency limited by the fast charge recombination. Here, we investigate the high-efficient photocatalytic hydrogen generation of (MoS2 –CdS)/Au and (MoS2 –CdS)/Pt hybrids, and demonstrate the plasmon-induced electron and energy transfer as well as the co-catalytic effect of metallic nanoparticles (NPs). In these hybrids, visible-light-harvester CdS NPs as well as plasmonic Au NPs or co-catalyst Pt NPs were grown on the monolayer MoS2 nanosheets. The photocatalytic H2 generation under visible light irradiation of (MoS2 –CdS)/Au and (MoS2 –CdS)/Pt is respectively 3.2 times and 2.4 times that of MoS2 –CdS. Intriguingly, the co-effect of Au NPs and Pt NPs leads to the 17 times enhancement. The plasmonic Au NPs in the hybrids play multiply significant roles to increase efficiency of H2 generation: (1) enhance light-harvesting and charge separation in the MoS2 –CdS subunit; (2) provide multiply plasmon-mediated hot electron injection channels; (3) amplify the co-catalyst effect of Pt. The present work offers a promising approach for the rational integration of multi-component photocatalyst to improve photocatalytic performance.